Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s13762-013-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, physiological responses and toxicity of nickel in plants

Abstract: The focus of the review is on the specific aspects of nickel's effects on growth, morphology, photosynthesis, mineral nutrition and enzyme activity of plants. The mobility of nickel in the environment and the consequent contamination in soil and water is of great concern. Also, the detrimental effects of excessive nickel on plant growth have been well known for many years. Toxic effects of nickel on plants include alterations in the germination process as well as in the growth of roots, stems and leaves. Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(82 citation statements)
references
References 75 publications
(105 reference statements)
1
77
0
1
Order By: Relevance
“…The similar shortcoming of time-consuming also arises in bioremediation of free cyanide. Phytoremediation, in contrast to other biology-based methods, has received considerable attention in remediating sites polluted with low to moderate levels of contamination (Akguc et al 2010;Cheng et al 2011;Ling et al 2011;Dubey and Shiwani 2012;Sreekanth et al 2013). As a natural, pumpand-treat system, phytoremediation is one of the very few technologies that can address a diverse range of media and contaminants simultaneously (Kord et al 2010;Ashraf et al 2011;Hegazy et al 2011;Dede et al 2012;Parween et al 2012;Karimi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The similar shortcoming of time-consuming also arises in bioremediation of free cyanide. Phytoremediation, in contrast to other biology-based methods, has received considerable attention in remediating sites polluted with low to moderate levels of contamination (Akguc et al 2010;Cheng et al 2011;Ling et al 2011;Dubey and Shiwani 2012;Sreekanth et al 2013). As a natural, pumpand-treat system, phytoremediation is one of the very few technologies that can address a diverse range of media and contaminants simultaneously (Kord et al 2010;Ashraf et al 2011;Hegazy et al 2011;Dede et al 2012;Parween et al 2012;Karimi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Excess Ni has been shown to cause a substantial decrease in all macroand micronutrients in leaves of different plants. Sreekanth et al (2013) also reported that for higher plants, Ni strongly influences metabolic reactions and has the capability to form reactive oxygen species which may cause oxidative stress. However, there is no information available for Ni in tea plant.…”
Section: Introductionmentioning
confidence: 97%
“…Toxic levels of Ni in plants range from 8 to 147 mg kg -1 (Gupta et al 2008) even though Ni is an essential micronutrient at very low contents (\50 lg g -1 in the plant tissue) for plant growth (Gupta et al 2008). The essentiality of Ni in plant is established by the documentation of various Ni deficiency symptoms as well as its physiological functions and critical roles in various enzymes in plants (Sreekanth et al 2013). Besides several beneficial roles of Ni in plant, it has been documented that Ni toxicity of plant grown in soil amended with large quantities of wastes, e.g., sewage and sludge (Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabiano et al, 2015). Su presencia en altas concentraciones inhibe el crecimiento de las plantas y puede llegar a producir clorosis 8 y necrosis (Sreekanth et al, 2013).…”
Section: Caracterización Inicial De Las Enmiendas Y Los Suelosunclassified